Optimal Control of a Modified Mathematical Model of Social Media Addiction - Juhari, Juhari; Alisah, Evawati; Safitri, Alisa Ayu; Sujarwo, Imam (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2024)
This research investigates the application of optimal control in the Susceptible, Exposed, Addicted, Recovery, Quit (SEA_1 A_2 RQ) model to address social media addiction. The primary objective is to develop an effective control strategy to reduce the prevalence of social media addiction. The methodology employs Pontryagin's maximum principle to formulate the optimal control problem, incorporating two time-dependent control variables: control (u_1) and treatment (u_2). The optimal control model is numerically simulated using the 4th-order Runge-Kutta method. Comparative analysis of the simulation results, with and without control, demonstrates significant differences in all population groups after four years. The findings reveal that implementing control (u_1) and treatment (u_2) markedly decreases the number of individuals addicted to social media, highlighting the efficacy of the proposed strategy in mitigating social media addiction.Keywords: optimal control; social media addiction model; Pontryagin maximum principle. AbstrakPenelitian ini mengkaji penerapan kontrol optimal pada model Susceptible, Exposed, Addicted, Recovery, model Quit (SEA_1 A_2 RQ)  untuk menangani kecanduan sosial media. Tujuan utama penelitian ini adalah untuk mengembangkan strategi kontrol yang efektif untuk mengurangi jumlah individu yang mengalami kecanduan media sosial. Metodologi penelitian ini menggunakan prinsip maksimum Pontryagin untuk merumuskan masalah kontrol optimal, yang menggabungkan dua variabel kontrol bergantung pada waktu: pengendalian (u_1) dan pengobatan (u_2). Model kontrol optimal disimulasikan secara numerik menggunakan metode Runge-Kutta orde 4. Analisis komparatif dari hasil simulasi, dengan dan tanpa kontrol, menunjukkan perbedaan yang signifikan pada semua kelompok populasi setelah empat tahun. Temuan tersebut mengungkapkan bahwa penerapan pengendalian (u_1) dan pengobatan (u_2) secara signifikan mengurangi populasi pengguna kecanduan sosial media, yang menyoroti kemanjuran strategi yang diusulkan untuk mengurangi kecanduan sosial media.Kata Kunci: kontrol optimal; model kecanduan media sosial; prinsip maksimum Pontryagin. 2020MSC: 49N90, 91D10, 92B05.